Hard breathable ophthalmic material and preparation method thereof
Through the synthesis of fluoro-containing silane monomers and the rod forming process using segmented radical polymerization, the mechanical properties and batch manufacturing efficiency of hard oxygen-permeable corneal contact lenses are improved, and the wear comfort and durability are improved through hydrophilic coating treatment, solving the problems of high manufacturing costs and poor mechanical performance in the prior art.
Patent Information
- Application Number
- CN202411870662.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
AI Technical Summary
The existing hard oxygen permeable corneal contact lenses have problems such as high manufacturing cost, poor mechanical properties, and strong sense of wearing foreign objects.
By synthesizing fluorine-containing silane monomers, integrating fluorine and silicon elements, and using segmented radical polymerization to perform the rod forming process to improve the mechanical properties of the material and batch manufacturing efficiency. At the same time, by subjecting the hydrophilic coating treatment of ophthalmic materials, the surface hydrophilicity and scratch resistance of the material are improved.
It achieves improved mechanical properties of the material, reduces manufacturing costs, improves wearing comfort and durability, and is suitable for manufacturing hard corneal contact lenses.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of corneal contact lenses, in particular to a hard gas-permeable ophthalmic material and a preparation method thereof. Background Art
[0002] Myopia is a common disease worldwide. Most people with myopia prefer contact lenses because of the inconvenience caused by myopia, such as the convenience of life, safety, reliability, low price and aesthetics. Compared with soft contact lenses, hard gas permeable contact lenses are durable, have better oxygen permeability, are easy to clean, and have the advantages of no dry eyes and more protein and oil deposition. Hard gas permeable contact lenses (i.e. orthokeratology lenses) with special structural design can also play a role in preventing and controlling myopia. Patients only need to wear them for about 8 hours at night, and their vision can be restored to near normal vision, and they no longer need to wear glasses for work and life during the day.
[0003] Rigid gas permeable contact lenses can effectively prevent and control the progression of myopia, are comfortable to wear for a long time, and are easy to handle, so they are favored by the majority of patients. The mainstream rigid gas permeable contact lenses on the market are all made of silicon-containing and fluorine-containing acrylate materials, which require the lenses to have high oxygen permeability, light transmittance and mechanical properties, especially orthokeratology lenses. This type of material is mainly composed of two main monomers containing silicon and fluorine, initiators, cross-linking agents and other additives (such as ultraviolet absorbers, colorants, etc.), which are mixed and cured by light, heat or radiation polymerization. After subsequent processing on an ophthalmic lathe, a rigid gas permeable contact lens can be obtained.
[0004] Rigid gas permeable contact lenses on the market still face many problems during use, such as: (1) the manufacturing cost of the material is relatively high; (2) during processing and use, they often break or break; (3) the material is highly hydrophobic, and there is a more obvious foreign body sensation when wearing it, requiring a longer period of patient adaptation; (4) long-term repeated wearing and cleaning will cause more and more scratches on the lens surface, which not only affects the visual effect, but may even cause lens damage. Summary of the invention
[0005] Technical problems solved by the present invention:
[0006] The invention is used to solve the problems of high manufacturing cost, poor mechanical properties and strong foreign body sensation of hard oxygen permeable corneal contact lenses existing in the prior art.
[0007] The technical solution adopted by the present invention is:
[0008] On the one hand, the present invention integrates fluorine and silicon elements into the same monomer by synthesizing fluorine-containing silane monomers, so that the silicon and fluorine content of each part of the material is consistent, so that the mechanical properties are more stable and it is not easy to crack when pressurized; then, the rod forming process is adopted by segmented free radical polymerization, which can stably realize the batch manufacturing of materials and avoid the cumbersome process and high cost of mold consumption brought by the traditional single-chip manufacturing process. On the other hand, the present invention forms a coating by coating the ophthalmic material through the hydrolysis, condensation and curing of KH-570 dispersed with titanium dioxide, which can improve the surface hydrophilicity and scratch resistance of the material on the basis of ensuring the optical performance and oxygen permeability.
[0009] First, the present invention provides a method for preparing a rigid gas-permeable ophthalmic material, comprising the following steps:
[0010] S1 synthesizes fluorinated silane monomers;
[0011] S2: Blending fluorinated silane monomer, crosslinking agent, small molecule monomer and auxiliary agent to obtain liquid A; taking part of liquid A and adding initiator to blend to obtain liquid B;
[0012] In an inert atmosphere of S3, liquid B is added dropwise to liquid A for prepolymerization, and then filled into a tubular mold for curing and molding to obtain an ophthalmic material.
[0013] According to some preferred embodiments, 3-(methacryloxy)propyltrimethoxysilane and chlorodimethyl-3,3,3-trifluoropropylsilane are subjected to a double hydrolysis condensation reaction to obtain methacryloxypropyltris(dimethyltrifluoropropylsiloxane)silane.
[0014] The reaction route is as follows:
[0015]
[0016] According to some preferred embodiments, a solvent is added to a reaction container, and a monomer blend of 3-(methacryloyloxy)propyltrimethoxysilane and chlorodimethyl-3,3,3-trifluoropropylsilane is added at room temperature, the monomer blend is added dropwise to the reaction container, refluxed to react, and after the reaction is completed, the mixture is allowed to stand and separate into layers, the organic layer is washed with water until it is neutral, and the finished product is obtained by distillation.
[0017] According to some preferred embodiments, the solvent is a methanol-water mixture, the mass ratio of methanol to water is 0.8-1.2:1, and the amount of solvent added is 0.4-0.6 times the total amount of monomers.
[0018] According to some preferred embodiments, the molar ratio of chlorodimethyl-3,3,3-trifluoropropylsilane to 3-(methacryloyloxy)propyltrimethoxysilane is 4-8:1.
[0019] According to some preferred embodiments, the dropping speed of the monomer blend liquid is 20 to 40 drops / min.
[0020] According to some preferred embodiments, the reflux reaction time is 8 to 24 hours.
[0021] According to some preferred embodiments, the crosslinking agent includes at least one of ethylene glycol dimethacrylate, neopentyl glycol dimethacrylate, triethylene glycol dimethacrylate, 1,3-di(1-methylvinyl)benzene, and trimethylolpropane triacrylate.
[0022] According to some preferred embodiments, the small molecule monomer includes at least one of hydroxyethyl methacrylate, styrene, benzyl methacrylate, methacrylic acid, and methyl methacrylate.
[0023] According to some preferred embodiments, the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, 2,5-dimethyl-2,5-bis(2-ethylhexanoic acid peroxide)hexane, tert-butyl peroxybenzoate, tert-butyl peroxy(2-ethylhexanoate), and tert-butyl peroxyneodecanoate.
[0024] According to some preferred embodiments, the auxiliary agent includes an ultraviolet absorber, and the ultraviolet absorber includes at least one of UV-P, UV-O, UV-9, UV-725, and UV-531.
[0025] According to some preferred embodiments, the auxiliary agent includes a colorant, and the colorant includes at least one of solvent green 3, pigment red 17, solvent yellow 18, and copper phthalocyanine.
[0026] According to some preferred embodiments, the raw material components are calculated by weight percentage, including 60-90% fluorine-containing silane monomer, 1-10% cross-linking agent, 3-10% small molecule monomer, 0.1-1% initiator, and 0.1-1% auxiliary agent. According to some preferred embodiments, prepolymerization: 40-60°C, 8-24h; curing: 60-90°C, 12-48h; molding: 100-150°C, 5-10h.
[0027] According to some preferred embodiments, after prepolymerization, it is filled into a tubular mold and then subjected to a curing and molding process.
[0028] According to some preferred embodiments, liquid B is prepared by adding 10 to 30% by mass of liquid A to an initiator and mixing evenly.
[0029] Second, the present invention provides a hard gas-permeable ophthalmic material obtained by the aforementioned preparation method.
[0030] According to some preferred embodiments, the surface of the ophthalmic material is treated with a hydrophilic coating; specifically,
[0031] The components of the hydrophilic coating raw materials include silane coupling agent (KH570), titanium dioxide, water, and ethanol;
[0032] The components of the hydrophilic coating raw materials are stirred and blended, and then sprayed and cured, and the process is repeated several times (1 to 5 times) to finally form a coating on the surface of the material;
[0033] Curing is done by thermal curing: 100-150°C, 10-60 minutes;
[0034] The curing method is UV curing: 100-150W, UV irradiation for 30-120min at a distance of 10-20cm.
[0035] The beneficial effects achieved by the present invention are:
[0036] The ophthalmic material prepared by the present invention has high fracture deformation, excellent air permeability and light transmittance, greatly improved wearing comfort and durability, and is suitable for manufacturing hard corneal contact lenses. Compared with commercially available materials, the process route is simple, the required equipment requirements are low, and the manufacturing cost is greatly reduced.
[0037] The hydrophilic coating provided by the present invention is firmly adhered to the surface of the material through hydrolysis, polycondensation and cross-linking of a silane coupling agent. Without significantly affecting the light transmittance and oxygen permeability of the material itself, the introduction of titanium dioxide can give the material more functions: on the one hand, it can give the material surface wettability to improve wearing comfort; on the other hand, it can improve the scratch resistance of the material surface, reduce the frequency of scratches that occur during the use of the product, and extend the service life of the lens. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0039] Fluorine-containing silane monomer (Example 1-2)
[0040] Example 1
[0041] TFDMCS: 3,3,3-trifluoropropyldimethylsilane
[0042] KH-570: 3-(Methacryloyloxy)propyltrimethoxysilane
[0043] NFMPS: Methacryloyloxypropyl tris(dimethyltrifluoropropylsiloxane)silane
[0044] 100g of a mixture of methanol and water (mixed in a mass ratio of 1:1) was added to the reactor. Under stirring at room temperature, 200g of a monomer mixture (the molar ratio of TFDMCS to KH-570 was 5:1) was added to the reactor at a rate of about 30 drops / min. The reaction temperature was controlled to be below 40°C, and the reaction was refluxed for 12 hours. After the reaction was completed, the liquid was allowed to stand for stratification and the water layer was removed. The organic layer solution was repeatedly washed with purified water until neutral, and the water layer was removed after standing. The residual low-boiling substances such as methanol and water were removed by reduced pressure distillation, and the monomer NFMPS was further distilled to obtain a yield of 63.28%.
[0045] Example 2
[0046] 100g of a mixture of methanol and water (mixed at a mass ratio of 0.8:1) was added to the reactor. Under stirring at room temperature, 167g of a monomer mixture (the molar ratio of TFDMCS to KH-570 was 6:1) was added to the reactor at a rate of about 30 drops / min. The reaction temperature was controlled to be below 40°C and the reaction was refluxed for 24 hours. After the reaction was completed, the liquid was allowed to stand for stratification and the water layer was removed. The organic layer solution was repeatedly washed with purified water until neutral, and the water layer was removed after standing. The residual low-boiling substances such as methanol and water were removed by reduced pressure distillation, and the monomer NFMPS was further distilled to obtain a yield of 68.31%.
[0047] Ophthalmic Materials (Examples 3-5)
[0048] Example 3
[0049] Weigh 79.6g NFMPS, 8g methacrylic acid, 7g neopentyl glycol dimethacrylate, 4g methyl methacrylate and 1g UV-725, stir and mix at room temperature to obtain liquid A, take about 20g of liquid A to dissolve 0.4g azobisisobutyronitrile to obtain liquid B. The remaining liquid A is loaded into a reflux reactor, stirred and heated to 55°C under nitrogen protection, liquid B is loaded into a constant speed dropping funnel, and the speed is adjusted to slowly drip into liquid A, dripping for about 2 hours, and reflux reaction is maintained for 12 hours to obtain a prepolymer liquid. The prepolymer liquid is poured into a tubular mold, deoxygenated and plugged, cured at 80°C for 48 hours, and then high-temperature treated at 150°C for 5 hours to obtain an ophthalmic material.
[0050] Example 4
[0051] Weigh 72.9g NFMPS, 11.8g methacrylic acid, 8.9g ethylene glycol dimethacrylate, 5.9g hydroxyethyl methacrylate and 0.01g solvent green 3, stir and mix at room temperature to obtain liquid A, take about 20g of liquid A to dissolve 0.3g azobisisobutyronitrile and 0.2g azobisisoheptanenitrile to obtain liquid B. The remaining liquid A is loaded into a reflux reactor, stirred and heated to 45°C under nitrogen protection, liquid B is loaded into a constant speed dropping funnel, and the speed is adjusted to slowly drip into liquid A, dripping for about 1 hour, and the reflux reaction is maintained for 20 hours to obtain a prepolymer solution. The prepolymer solution is poured into a tubular mold, deoxygenated and plugged, cured at 90°C for 12 hours, and then high-temperature treated at 120°C for 5 hours to obtain an ophthalmic material.
[0052] Example 5
[0053] Weigh 85.7g NFMPS, 2g methyl methacrylate, 5g neopentyl glycol dimethacrylate, 2g benzyl methacrylate and 5g hydroxyethyl methacrylate, stir and mix at room temperature to obtain liquid A, take about 20g of liquid A to dissolve 0.14g peroxy (2-ethylhexanoic acid) tert-butyl ester and 0.17g peroxy neodecanoic acid tert-butyl ester to obtain liquid B. The remaining liquid A is loaded into a reflux reactor, stirred and heated to 40°C under nitrogen protection, liquid B is loaded into a constant speed dropping funnel, and the speed is adjusted to slowly drip into liquid A, dripping for about 30 minutes, and the reflux reaction is maintained for 8 hours to obtain a prepolymer solution. The prepolymer solution is poured into a tubular mold, deoxygenated and plugged, cured at 60°C for 48 hours, and then molded at 100°C for 10 hours to obtain an ophthalmic material.
[0054] Hydrophilic coating (Examples 6-8)
[0055] The hard oxygen-permeable ophthalmic material prepared in Example 3 is used as a substrate to be processed into a sheet with a thickness of 0.2 mm, and the surface is polished and cleaned. The coating liquid is evenly applied to the surface of the substrate by a spraying process and cured by heat or ultraviolet.
[0056] Example 6
[0057] A peroxo titanium complex solution was prepared by mixing tetraisopropoxytitanium, H2O2 and H2O in a volume ratio of 12:90:200, respectively. The pH value was then adjusted to 7.0, and the resulting solution was refluxed for 10 hours to obtain anatase crystalline titanium dioxide sol, which was freeze-dried and ground and sieved to obtain titanium dioxide powder.
[0058] Example 7
[0059] 5 g of ethanol-dispersed nano-anatase titanium dioxide sol (concentration 10 mg / mL), 50 g of 95% ethanol and 0.1 g of methacryloxypropyltrimethoxysilane were stirred at room temperature for 1 hour to obtain a coating liquid. The peroxide titanium complex solution in Example 6 was first sprayed onto the above substrate sheet as a pre-coating layer, and then the coating liquid was sprayed, and cured at 120° C. for 30 minutes to obtain the first coating layer, and the spraying and curing were repeated 3 times under the same conditions.
[0060] Example 8
[0061] 10g of ethanol-dispersed nano-anatase crystalline titanium dioxide sol (concentration 10mg / mL), 45g of 95% ethanol and 0.2g of methacryloxypropyltrimethoxysilane were stirred at room temperature for 1h to obtain a coating liquid. The peroxide titanium complex solution in Example 6 was first sprayed onto the above substrate sheet as a pre-coating layer, and then the coating liquid was sprayed, and irradiated and cured for 1h under a 130W ultraviolet lamp at a distance of 15cm to obtain the first layer of coating, and the spraying and curing were repeated 5 times under the same conditions.
[0062] Test example
[0063] 1. The ophthalmic materials prepared in Examples 3-5 were used as samples for testing. The results are shown in Table 1.
[0064] Sample A: Process a test sample with a thickness of 0.5 mm, a length of 13 mm, and a width of 8 mm, and measure the flexural modulus according to the method of GB / T9341-2008;
[0065] Sample B: The sample was processed with a thickness of 6 mm and a diameter of 12 mm, polished, and the hardness was measured according to the 9 Shore D hardness method in GB / T11417.6-2012, and the contact angle was measured according to the 4.6 bubble capture method in GB / T 11417.7-2012;
[0066] Sample C: Single-curve lens with a total diameter of 9.5mm, a base radius of 7.8mm, and a center thickness of 0.2mm was processed. The force at compression fracture and the deformation rate at compression fracture were measured according to the bending deformation and fracture method of 8 hard lenses in GB / T11417.6-2012, and the maximum deformation rate was set to 90%; the visible light transmittance was measured according to the method of GB / T11417.5-2012;
[0067] Sample D: Four lenses of different thicknesses were processed with a total diameter of 10.6 mm, a base radius of 8.6 mm, and a center thickness of 0.1 mm to 0.4 mm. The oxygen permeability coefficient was determined according to the polarographic method in 4.3 of GB / T 11417.7-2012.
[0068] Table 1
[0069]
[0070] 2. The ophthalmic material coatings prepared in Examples 3 and 7-8 were used as samples for measurement. The visible light transmittance was measured according to the method of GB / T11417.5-2012, the contact angle was measured according to the bubble capture method in 4.6 of GB / T 11417.7-2012, the scratch resistance was measured according to 6.3 Method B in SN / T 4449-2016, and the adhesion was measured according to the method of GB / T 9286-2021. The results are shown in Table 2.
[0071] Table 2
[0072] index Example 3 (substrate) Example 7 Example 8 Visible light transmittance / % 92.31 90.21 89.45 Contact angle / ° 48 32 24 Scratch resistance / grade 5 3 2 Adhesion / Grade / 0 0
Claims
1. A method for preparing a rigid gas-permeable ophthalmic material, characterized in that: The steps include: S1 synthesizes fluorinated silane monomers; S2: Blending fluorinated silane monomer, crosslinking agent, small molecule monomer and auxiliary agent to obtain liquid A; taking part of liquid A and adding initiator to blend to obtain liquid B; In an inert atmosphere of S3, liquid B is added dropwise to liquid A for prepolymerization, and then filled into a tubular mold for curing and molding to obtain an ophthalmic material.
2. The method for preparing the rigid gas-permeable ophthalmic material according to claim 1, characterized in that: S2 includes at least one of features (S2-1) to (S2-5): (S2-1) the cross-linking agent includes at least one of ethylene glycol dimethacrylate, neopentyl glycol dimethacrylate, triethylene glycol dimethacrylate, 1,3-di(1-methylvinyl)benzene, and trimethylolpropane triacrylate; (S2-2) the small molecule monomer includes at least one of hydroxyethyl methacrylate, styrene, benzyl methacrylate, methacrylic acid, and methyl methacrylate; (S2-3) the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, 2,5-dimethyl-2,5-bis(2-ethylhexanoic acid peroxide)hexane, tert-butyl peroxybenzoate, tert-butyl peroxy(2-ethylhexanoate), and tert-butyl peroxyneodecanoate; (S2-4) the auxiliary agent includes an ultraviolet absorber, and the ultraviolet absorber includes at least one of UV-P, UV-O, UV-9, UV-725, and UV-531; (S2-5) The auxiliary agent includes a colorant, and the colorant includes at least one of solvent green 3, pigment red 17, solvent yellow 18, and copper phthalocyanine.
3. The method for preparing the rigid gas-permeable ophthalmic material according to claim 1, characterized in that: S2 includes features (S2-6): (S2-6) The components of the raw materials are calculated by weight percentage, including 60-90% of fluorine-containing silane monomer, 1-10% of cross-linking agent, 3-10% of small molecule monomer, 0.1-1% of initiator, and 0-1% of auxiliary agent.
4. The method for preparing the rigid gas-permeable ophthalmic material according to claim 1, characterized in that: The mass of liquid B is 10-30% of the mass of liquid A.
5. The method for preparing the rigid gas-permeable ophthalmic material according to claim 1, characterized in that: S3 includes at least one of features (S3-1) to (S3-4): (S3-1) Prepolymerization: 40-60° C., 8-24 h; (S3-2) Curing: 60-90° C., 12-48 h; (S3-3) Molding: 100-150° C., 5-10 h; (S3-4) The diameter of the tubular mold is 15mm to 20mm and the length is 10 to 30mm.
6. The method for preparing a rigid gas-permeable ophthalmic material according to any one of claims 1 to 5, characterized in that: S1 includes features (S1-1): (S1-1) Synthesis of fluorine-containing silane monomer: 3-(methacryloyloxy)propyltrimethoxysilane and chlorodimethyl-3,3,3-trifluoropropylsilane are subjected to a double hydrolysis condensation reaction to obtain methacryloxypropyltris(dimethyltrifluoropropylsiloxy)silane.
7. The method for preparing the rigid gas-permeable ophthalmic material according to claim 6, characterized in that: S1 includes features (S1-2): (S1-2) Add a solvent into a reaction container, and add a monomer mixture of 3-(methacryloyloxy)propyltrimethoxysilane and chlorodimethyl-3,3,3-trifluoropropylsilane at room temperature, add the monomer mixture dropwise into the reaction container, reflux reaction, and after the reaction is completed, stand to separate the layers, wash the organic layer with water until it is neutral, and obtain the finished product by distillation.
8. The method for preparing the rigid gas-permeable ophthalmic material according to claim 7, characterized in that: S1 includes at least one of features (S1-3) to (S1-6): (S1-3) the solvent is a methanol-water mixture, the mass ratio of methanol to water is 0.8 to 1.2:1, and the amount of solvent added is 0.4 to 0.6 times the total amount of monomers; (S1-4) the molar ratio of chlorodimethyl-3,3,3-trifluoropropylsilane to 3-(methacryloyloxy)propyltrimethoxysilane is 4 to 8:1; (S1-5) The dropping speed of the monomer blend liquid is 20 to 40 drops / min; (S1-6) Reflux reaction time: 8 to 24 hours.
9. A hard gas-permeable ophthalmic material obtained by the preparation method according to any one of claims 1 to 8.
10. The rigid gas-permeable ophthalmic material according to claim 9, characterized in that: The surface of the ophthalmic material is treated with a hydrophilic coating; the hydrophilic coating comprises at least one of the features (A) to (D): (A) The components of the hydrophilic coating raw materials include silane coupling agent, titanium dioxide, water and ethanol; (B) stirring and blending the components of the hydrophilic coating raw material, and then spraying and curing, repeating this process several times, and finally forming a coating on the surface of the material; (C) Curing: thermal curing conditions: temperature 100-150°C, time 10-60 minutes; (D) Curing: UV curing conditions: UV lamp power 100-150W, distance between light source and sample 10-20cm, irradiation time 30-120min.